Effects of Surface Modificationon the Suspension Stability and Thermal Conductivity of Carbon Nanotubes Nanofluids. (May 2015) - Zhang, P.; Hong, W.; Wu, J.F.; Liu, G.Z.; Xiao, J.; Chen, Z.B.; Cheng, H.B.
Abstract: The composite carbon nanotubes (CCNTs) were synthesized by surface modification of the as-synthesized carboxyl-functionalized carbon nanotubes (f-CNTs) with the polyethylene glycol, and the composite carbon nanotubes-based nanofluids(CCNTs-based nanofluids) were prepared with the as-synthesized CCNTs and ethylene glycol. The surface molecular structure, surface morphology of the CCNTs were characterized by FourierTransform Infrared Spectroscopy, Field Emission Scanning Electron Microscope and Transmission Electron Microscopy. The suspension stability and thermal conductivity enhancement ratio of the CCNTs-based nanofluids were characterized viathe thermal conductivity variation method. The results show that suspension stability of the CCNTs-based nanofluids was greatly improved by surface modification of the carbon nanotubes; the thermal conductivity of the CCNTs-based nanofluids was further enhanced and became more stableby surface modification.